The spread of infectious diseases in migration routes between caravans and resident communities: Modelling yellow fever in Central America - Sabrina Soares Simon; Marcos Amaku; Eduardo Massad (The Journal of Climate Change and Health)
Introduction: Climate-sensitive diseases are significantly affected by weather patterns and the social consequences of a changing climate. In this context, epidemics and human mobility can interact, leading to unpredictable impacts on both human and planetary health. Methods: To investigate the impact of yellow fever (YF) vaccination in the context of an outbreak and its association with migration, we use a SEIRV-SEI compartmental deterministic model for humans and vectors and numerical simulations applied to three coupled populations - caravans, endemic and disease-free communities. Two scenarios are evaluated with different vaccination coverage levels at endemic communities and in caravans. Results: When communities endemic to YF are the source of migration, herd immunity is critical, but vaccinating caravans is by far the most significant intervention to protect migrants and disease-free communities upwards from the risk of YF introduction. Conclusion: Preventing outbreaks of climate-sensitive infectious diseases in the context of migration must be a joint effort of common interest. Maintaining vaccination coverage at recommended levels combined with the continued effort to vaccinate people on the move is the only intervention that can prevent a health crisis. Therefore, vaccination against climate-sensitive diseases should be considered climate adaptation.